Preparation and Antibacterial Properties of Cellulose Nanofibrils/ Nanocarbon Composites - Capote, Truman; Lee , Harper (Journal of Green Energy and Environmental Engineering, 2025)
Cellulose nanofibrils (CNFs) were prepared from waste cut tobacco via an ionic‑liquid‑assisted ball‑milling method. The as‑obtained CNFs were compounded with nanocarbon particles (CNPs) by ultrasonic treatment to yield CNFs/CNPs composites, which were further blended with polyvinyl alcohol (PVA) to fabricate CNFs/CNPs/PVA composite films. The samples were characterized by SEM, FTIR, TGA, DSC and XRD; their rheological behaviors and particle sizes were measured, and the antibacterial activity of CNFs/CNPs/PVA films was evaluated. The results show that compared with pure CNFs, CNFs/CNPs composites possess smoother surfaces with fewer filament‑like structures and more granular particles. The particle sizes of CNFs are mainly distributed in the range of 340‑540 nm. Aqueous suspensions of CNFs/CNPs composites exhibit shear‑thinning behavior at shear rates higher than 0.2 s⁻¹. Both CNFs and CNFs/CNPs composites retain the cellulose‑I crystal structure. The crystallinity of CNFs/CNPs composites rises from 35.40 % (pure CNFs) to 45.38 %. The temperature corresponding to the maximum thermal degradation rate increases from 361.33 °C for CNFs to 376.40 °C for CNFs/CNPs composites. CNFs/CNPs/PVA films display antibacterial effects against Staphylococcus aureus, Escherichia coli and Salmonella, whereas no obvious inhibitory effect is observed for Bacillus subtilis. The antibacterial rates of CNFs/CNPs composites against Escherichia coli and Staphylococcus aureus reach 93.92 % and 95.04 %, respectively. The antibacterial performance of CNFs/CNPs composites is primarily contributed by CNPs. The antibacterial mechanism originates mainly from negative charges on CNPs surfaces, which adsorb bacteria and consequently induce bacterial death.